Menopausal Hormone Replacement Therapy and the Risk of Ovarian Cancer: A Meta-Analysis - Liu, Yang; Ma, Lan; Yang, Xiaoling; Bie, Jia; Li, Dongya; Sun, Chunyi; Zhang, Jie; Meng, Yushi; Lin, Jie (Frontiers in Endocrinology, 2019)
Background: Findings by epidemiologic studies on menopausal hormone replacement therapy (HRT) and the risk of ovarian cancer are inconsistent. This study aimed to assess the association of menopausal HRT with the risk of ovarian cancer by histological subtype. Methods: A literature search was performed in PubMed, Web of Science and EmBase for relevant articles published from inception to August 2018. Pooled relative risk ratios (RRs) with 95% confidence intervals (CIs) were determined with a random-effects model. Results: Thirty-six studies involving 4, 229, 061 participants were included in this meta-analysis. The pooled RR of ovarian cancer was 1.29 (95%CI 1.19-1.40, I2=57.4%) for menopausal HRT. In subgroup analysis by study design, pooled RRs of ovarian cancer in cohort and case-control studies were 1.35 (95%CI 1.19-1.53) and 1.24 (95%CI 1.11-1.38), respectively. In subgroup analysis by continent, association of menopausal HRT with ovarian cancer was significant for North America (1.41[1.23-1.61]), Europe (1.22[1.12-1.34]), and Asia (1.76[1.09-2.85]), but not Australia (0.96[0.57-1.61]). Association differed across histological subtypes. Increased risk was only found for two common types, including serous (1.50[1.35-1.68]) and endometrioid (1.48[1.13-1.94]) tumors. Conclusion: This meta-analysis suggests that menopausal HRT may increase the risk of ovarian cancer, especially for serous and endometrioid tumors.